2021
DOI: 10.16965/ijar.2021.176
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Dermatoglyphic Patterns of Fingers in Patients with Myocardial Infarction

Abstract: Background: The myocardial infarction (MI), the most common manifestation of coronary artery disease remains as a major cause of mortality in both developed and developing countries. The people without known major risk factors can be screened for MI with a simple and cost-effective tool which will be helpful in developing countries to reduce the mortality. Dermatoglyphic patterns in clinical conditions have been studied so far and their relationship is established in the literature. Dermatoglyphics has been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found the frequency of whorls is a characteristic dermatoglyphic pattern of CAD which could be very useful in its early diagnosis. In 2011 Arun Kumar et al [18] concluded that the percentage of loop, arch, and whorls is 54.9%, 8.3%, and 36.8%, respectively in myocardial infarction and 59.4%, 13.2%, and 27.4%, respectively, in controls. Thus, there is a decrease in loops and arches with an increase in whorls in most of the digits of both hands in MI.…”
Section: Resultsmentioning
confidence: 99%
“…They found the frequency of whorls is a characteristic dermatoglyphic pattern of CAD which could be very useful in its early diagnosis. In 2011 Arun Kumar et al [18] concluded that the percentage of loop, arch, and whorls is 54.9%, 8.3%, and 36.8%, respectively in myocardial infarction and 59.4%, 13.2%, and 27.4%, respectively, in controls. Thus, there is a decrease in loops and arches with an increase in whorls in most of the digits of both hands in MI.…”
Section: Resultsmentioning
confidence: 99%